2018
DOI: 10.1101/456491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordinated demethylation of H3K9 and H3K27 is required for rapid inflammatory responses of endothelial cells

Abstract: C.K.G.), kanki@lsbm.org (Y.K.) SUMMARY Lysine 9 di-methylation and lysine 27 tri-methylation of histone H3 (H3K9me2 and H3K27me3) are generally linked to gene repression. However, the functions of repressive histone methylation dynamics during inflammatory responses remain enigmatic. We found that tumor necrosis factor (TNF)-α rapidly induces the co-occupancy of lysine demethylases 7A (KDM7A) and 6A (UTX) with nuclear factor kappa-B (NF-κB) recruited elements in human endothelial cells. KDM7A and UTX demethyla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 110 publications
1
13
0
Order By: Relevance
“…UTX has been functionally linked to many physical and pathological processes, including embryonic development, 39,40 tumor progression, [41][42][43][44] inflammation, 45 and stem cell differentiation 46,47 by H3K27 demethylation-dependent or -independent gene transcription. Although UTX was shown to be required for nuclear factor kB (NF-kB)-dependent inflammatory response of ECs, 48 the regenerative regulation mediated by UTX in SCI is still unclear. We first examined the changes of several key epigenetic regulators post SCI, and we found that the mRNA level of UTX increased significantly post SCI, whereas the changes of other epigenetic factors are variable at different time points post SCI.…”
Section: Discussionmentioning
confidence: 99%
“…UTX has been functionally linked to many physical and pathological processes, including embryonic development, 39,40 tumor progression, [41][42][43][44] inflammation, 45 and stem cell differentiation 46,47 by H3K27 demethylation-dependent or -independent gene transcription. Although UTX was shown to be required for nuclear factor kB (NF-kB)-dependent inflammatory response of ECs, 48 the regenerative regulation mediated by UTX in SCI is still unclear. We first examined the changes of several key epigenetic regulators post SCI, and we found that the mRNA level of UTX increased significantly post SCI, whereas the changes of other epigenetic factors are variable at different time points post SCI.…”
Section: Discussionmentioning
confidence: 99%
“…These observations also suggest that KDM7A and RHOJ may possess mutually independent prometastatic functions. Prior studies, based on either single-locus or genome-wide gene expression analysis, have suggested that KDM7A is involved in the regulation of target genes downstream of the NF-κB pathway ( Higashijima et al, 2020 ) and the Wnt/β-catenin pathway ( Yang et al, 2019a ; Liu et al, 2020 ), which allude to a broader promalignancy mechanism. Small-molecule inhibitors of KDM7A have been discovered although their therapeutic potentials in breast cancer have yet to be explored ( Gerken et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence is given by TNFα mediated inflammation, upon which rapid removal of repressive histone marks H3K9me2/me3 and H3K27me3 leads to activation of Nf-kB and other inflammatory signaling cascades via KDM7A and UTX [ 54 ]. This is in line with our hypothesis of gene induction of heterochromatin repressed inflammatory signaling genes.…”
Section: Discussionmentioning
confidence: 99%